Falla en la prestación del servicio médico en la ciudad de Bogotá (2015)
This work will be displayed as a thesis to obtain requisite degree in Administrative Law Specialization this failure will develop the delivery of medical services in Colombia, will touch issues like that generates causes the failure of medical services in the health system in Bogotá and that legal code was generated to control this error that are usually involved the EPS and clinics in the city of Bogotá, also determine who is the alleged failure and tested in the health system fails to develop this thesis we have to go find and interpret about what has expressed the State Council in its Section III concerning the topic, and previous to sitting on it, leading to develop conclusion that generated the fault the provision of medical services specifically in Bogota and steps taken by the state to control or eliminate these problems affecting the country, and consequently that damages can eventually cause the Colombian population.